THE ANALYSIS OF CONSTITUENT MATERIALS OF THE NAOS DOORS BELONGING TO THE WOODEN CHURCH FROM PETRINDU, SALAJ COUNTY - BRATU, Ioan; MĂRUȚOIU, Constantin; POSTOLACHE, Dana Luminița; TANASELIA, Claudiu; NEMEŞ, Olivia Florena (Studia Universitatis Babeș-Bolyai Chemia, 2017)
In order to preserve and restore the door that separate the Naos and Pronaos belonging to the wooden church of Petrindu, Salaj County, the scientific expertise (with FTIR, XRF spectroscopy and restoring) of the wooden stage and of the painting materials (ground, pigments) was performed. FTIR spectroscopy offers information about the wooden stage whereas XRF and FTIR spectroscopic methods were employed for structural painting materials characterization. These structural data can be correlated with the artistic, theological and historical analysis of this religious patrimony object. After obtaining information about wooden stage and the painting materials, the door was restored.